Challenges Encountered in the Implementation of the Education Program among Senior High School Students in The Philippines - Patricia Mae N. Gurobat; Jenevieve D. Lumbu-an (Indonesian Journal of Educational Research and Technology, 2022)
The K-12 Education Program is a new education curriculum in the Philippines that further develops students' skills and concepts in different strands to prepare them for tertiary education and exhibit competence as lifelong learners; however, its implementation has several drawbacks. Thus, researchers identified and analyzed the typical issues that Sultan Kudarat State University –Laboratory High School SHS students faced in implementing the K-12 Education Program and dealt with those challenges and coping strategies. This study employed the qualitative research design, specifically, the phenomenological approach. Focus group discussion and individual interviews were employed to get the needed data. Based on the study findings, students perceive the new curriculum as a significant burden, with the top challenges of having more years in high school, lack of assistance, and learning facilities. They also agreed on the benefits of the new educational system, which include more knowledge and learning, increased competency, and future career chances. Despite the difficulty adjusting to the K-12 program, they tend to cope with the challenges using various coping strategies such as time management, adjustment, acceptance, peer support, as they are aware of the program's value to their academic advancement. As a result, this research can assist students in preparing for the obstacles they may face in senior high school and recommend possible coping mechanisms.